Some properties of nonlinear oscillations in a diode in the space charge–limited current regime - Akimov, P.V.; Ender, A.Ya.; Kolinsky, H.; Kuznetsov, V.I.; Schamel, H. (Вопросы атомной науки и техники, 2000)
Both the initial and late non-linear stages of the oscillation process in a beam vacuum diode in the space-charge-limited current regime are numerically investigated. Two different numerical methods are applied: Birdsall's code (B-code) and Ender-Kuznetsov code (EK-code). The capabilities of both codes are compared. The high accuracy of the EK-code gives an opportunity to build dispersion branches of instability. The domain of the parameter values, when simultaneously several stable dynamical states (limit cycles) exist, is found. A sharp decrease in the amplitude of oscillations is revealed already under a comparatively small (about 2.5%) spread in velocities of the electron beam.